Peran Pembina Lapas Narkotika Dalam Penanaman Pendidikan Karakter Islami Bagi Warga Binaan - Muhamamd Fauzan Nafis; Ngismatul Choiriyah; Nashihatud Diniyah Jahro; Lailatul Fithriyah Azzakiyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Palangkaraya, 2025)
The problem behind this research is the lack of supervisors in the Class II A Kasongan prison, so that coaching cannot run optimally and this has an impact on prisoners who have been released from prison (returned to the community), still behave criminally, this is proven with the prisoners who are back to being drug suspects again. The purpose of this study is to describe 1) What is the role of narcotics prison supervisors in instilling Islamic character education for narcotics abuse convicts in Class II A Kasongan penitentiary. 2) Knowing the inhibiting factors for narcotics prison supervisors in instilling Islamic character education for narcotics abuse convicts in class II A Kasongan correctional institutions. 3) Knowing the efforts made by narcotics prison supervisors in planting Islamic character education for narcotics abuse convicts in Class II A Kasongan correctional institutions. This research is a qualitative research with a descriptive approach. The data collection techniques used are interviews, observation and documentation. The results of this study 1) The role of the Kasongan class II A narcotics prison supervisor is as a coach or mentor for prisoners so that they become aware and can play a role in social life after their detention period is over. 2) The inhibiting factor that occurs in the development of narcotics prisoners in the Class II A Kasongan prison is the lack of existing supervisors, making it quite difficult for prison residents to get guidance from someone who is competent in spiritual guidance. 3) The efforts that have been made by the prison itself are collaborating with the Ministry of Religion and the administrators of several mosques in the Kasongan area to add outside coaches to help carry out coaching in prisons.